INOVASI KEBIJAKAN REDAKSIONAL DALAM MENERAPKAN JURNALISME DATA PADA MEDIA DARING ALINEA.ID - Rizki Febianto, (2020)
Data journalism is an innovation of changing trends in the news structure of online media. At the beginning of its development, the online media carried out concise, sustainable, sensational reporting practices, and only concerned with the large number of clickers and viewers. This raises a problem, where online journalism is seen as unable to display its quality. Until finally data journalism emerged, bringing changes in news writing trends to become deeper, comprehensive, and include various data to support the quality of news content. This qualitative research uses the theory of innovation diffusion introduced by Everett M Rogers to explain how the process of adopting data journalism in online media, as well as how editorial policy innovations are carried out to support the application of data journalism. Case studies will be carried out on the online media Alinea.id because the media applies data journalism as the basis for the news information. This study concludes that there are editorial policy innovations carried out by Alinea.id to support data journalism, namely the application of Alinea tools, which are able to be a reference for the editorial staff to determine the coverage that will be aired, as well as enrich the news topics of data journalism. In the aspect of presenting the data, Alinea also made an innovation by presenting a content called AIR (Alinea Interactive Report). Presentation of data in AIR is packaged creatively and attractively, has animated features in it, makes images and writing that can move if the reader clicks on it. AIR is an innovation from the presentation of data which was previously only in the form of diagrams and pictures.